2009
DOI: 10.1590/s0034-75902009000300003
|View full text |Cite
|
Sign up to set email alerts
|

Uma agenda brasileira para os estudos em aprendizagem organizacional

Abstract: RESUMOO presente artigo apresenta os resultados mais significativos obtidos em um estudo que teve como principal objetivo explorar os discursos formadores do campo de conhecimento da Aprendizagem Organizacional e que utilizou a metodologia denominada metatriangulação. A seleção das fontes de pesquisa procurou assegurar a cobertura dos periódicos nacionais e dos anais de congresso mais expressivos e consolidados, na área de conhecimento de administração, que abordaram este tema, no período de [2001][2002][2003]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
25

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 32 publications
0
16
0
25
Order By: Relevance
“…Some studies have proposed to analyze academic production on Organizational Learning at work context in Brazil, such as Loiola and Bastos (2003), Antonello and Godoy (2009), and Godoy and Antonello (2011). Focused specifically on Informal Learning only the study by Reatto and Godoy (2015) was found.…”
Section: Previous Studies About Scientific Production On Learning In mentioning
confidence: 99%
See 4 more Smart Citations
“…Some studies have proposed to analyze academic production on Organizational Learning at work context in Brazil, such as Loiola and Bastos (2003), Antonello and Godoy (2009), and Godoy and Antonello (2011). Focused specifically on Informal Learning only the study by Reatto and Godoy (2015) was found.…”
Section: Previous Studies About Scientific Production On Learning In mentioning
confidence: 99%
“…Following the same premises and methodological choices as Antonello and Godoy (2009) study, there is also Godoy and Antonello (2011) study named "Mapping of Organizational Learning in Brazil: a multiparadigmatic review" presenting an analysis of studies with the same scope as Antonello and Godoy's (2009) but expanding the investigation and finding that, from the total 94 papers, 21 have been categorized as studies focused on investigating current formal and informal work practices present in the informal Organization structures, a category in which probably the studies approach informal learning, but not only these ones. Finally, the study by Reatto and Godoy (2015) is highlighted, proposing the investigation of scientific production on Informal Learning framework specifically in journals ranked as B2 or higher according to Capes rank, from 2006 through 2012.…”
Section: Previous Studies About Scientific Production On Learning In mentioning
confidence: 99%
See 3 more Smart Citations